Feasibility and Functional Outcomes of Children and Adolescents Undergoing Preoperative Chemotherapy Prior to a Limb-Sparing Procedure or Amputation. Issue 1 (January 2017) - Corr, Angela Meyer; Liu, Wei; Bishop, Michael; Pappo, Alberto; Srivastava, Deo Kumar; Neel, Michael; Rao, Bhaskar; Wilson, Terry; Ness, Kirsten K.
Abstract : Background: Survivors of lower extremity (LE) malignancies experience functional deficits. Purpose: The purpose of this prospective clinical trial was to determine feasibility and functional outcomes of adding prehabilitation during the 10- to 12-week period prior to a planned surgery to remove the tumor in children and adolescents with an LE sarcoma. Design: Pilot study. Setting: St. Jude Children's Research Hospital. Patients: Participants included 14 individuals between the ages of 8 and 20 years who had a diagnosis of an LE sarcoma. Participant outcomes were compared with a control group of 35 individuals treated for osteosarcoma who underwent the same functional assessments but no prehabilitation. Intervention: Participants in the intervention group received strengthening exercises and mobility training 3 times per week for 30 to 60 minutes for 10 to 12 weeks preoperatively. Measurements: Participants completed the Functional Mobility Assessment (FMA) and measures of strength and range of motion (ROM) of bilateral LEs at baseline, after 10 to 12 weeks of preoperative physical therapy (PT), and at 20 to 22 weeks. Results: Twelve participants completed at least 50% of their schedule prehabilitative sessions. Participants in the intervention group scored significantly better on the FMA than participants in the control group at weeks 20 to 22 (35.6 vs 25.7, P = .0267). No significant difference was found in ROM or strength. Limitations: Because of this study being a pilot study, the sample size was small. Therefore, we cannot infer generalizability. Conclusions: Findings suggest that those with a diagnosis of an LE malignancy awaiting a limb-sparing procedure or amputation participate in at least 50% of scheduled PT sessions and benefit from them.